2016
DOI: 10.1016/j.neulet.2016.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-synuclein (SNCA) polymorphisms exert protective effects on memory after mild traumatic brain injury

Abstract: Problems with attention and short-term learning and memory are commonly reported after mild traumatic brain injury (mTBI). Due to the known relationships between α-synuclein (SNCA), dopaminergic transmission, and neurologic deficits, we hypothesized that SNCA polymorphisms might be associated with cognitive outcome after mTBI. A cohort of 91 mTBI patients one month after injury and 86 healthy controls completed a series of cognitive tests assessing baseline intellectual function, attentional function, and memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Fifty-four publications described prospective cohort studies 16 , 17 , 19–24 , 26 31 , 34 , 35 , 37 , 38 , 40–44 , 46 53 , 55 , 57–64 , 66 – 69 , 71 , 73–80 , 83 Fourteen studies were retrospective cohort studies on banked DNA samples 18 , 25 , 32 , 33 , 36 , 39 , 45 , 54 , 56 , 65 , 70 , 72 , 82 , 83 Study location also varied significantly, with the most commonly reported country of origin being the United States ( n = 43). Twenty-six studies included fewer than 100 patients 17 , 19 , 24 , 26 , 27 , 32 , 35 , 37 , 40 , 42–44 , 47 , 50–53 , 57 , 67–69 , 71 , 74 , 76 , 78 , 80 Seven studies were published conference abstracts. 25 , 44 , 62 , 66 , 74 , 76 , 78 The diversity and number of studies make it difficult to provide summary tables in the body of the article, and all of these data are therefore provided as Supplementary Materials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty-four publications described prospective cohort studies 16 , 17 , 19–24 , 26 31 , 34 , 35 , 37 , 38 , 40–44 , 46 53 , 55 , 57–64 , 66 – 69 , 71 , 73–80 , 83 Fourteen studies were retrospective cohort studies on banked DNA samples 18 , 25 , 32 , 33 , 36 , 39 , 45 , 54 , 56 , 65 , 70 , 72 , 82 , 83 Study location also varied significantly, with the most commonly reported country of origin being the United States ( n = 43). Twenty-six studies included fewer than 100 patients 17 , 19 , 24 , 26 , 27 , 32 , 35 , 37 , 40 , 42–44 , 47 , 50–53 , 57 , 67–69 , 71 , 74 , 76 , 78 , 80 Seven studies were published conference abstracts. 25 , 44 , 62 , 66 , 74 , 76 , 78 The diversity and number of studies make it difficult to provide summary tables in the body of the article, and all of these data are therefore provided as Supplementary Materials.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies documented the relationship between various SNPs and nonglobal patient outcomes (i.e., neuropsychiatric, behavioral, and other). 57 , 60 , 66 , 67 , 69 , 71–73 , 82 , 83 The targets for these polymorphisms included: ACE, 57 various oxytocin SNPs, 66 PERIOD3, 67 ATP binding cassette, 60 nitric oxide synthase-3 (NOS3), 69 alpha synuclein (SNCA), 71 kidney and brain expressed protein (KIBRA), 72 BMX, 73 methyenetetrahydrofolate reductase (MTHFR), 82 and adenosine A1 receptor. 83 Full details can be found in Supplementary Appendix 9 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to TBI is a risk factor for PD, with increased age at injury, loss of consciousness, and severity of TBI contributing to greater risk (Crane et al, 2016;Gardner et al, 2014;Jafari et al, 2013;Lee et al, 2015;Lee et al, 2013). Genetic factors also link TBI and PD -presence of α-synuclein polymorphisms and polymorphic mixed-dinucleotide repeats were associated with reduced PD risk and improved cognitive outcome after mild TBI exposure (Goldman et al, 2012;Shee et al, 2016). An important role for α-synuclein in formation of the soluble N-ethylmaleimidesensitive factor attachment protein receptor (SNARE) complex (Burre et al, 2010;Chandra et al, 2005) and regulation of presynaptic vesicular pools (Murphy et al, 2000) connects αsynuclein to neurotransmitter exocytosis, with implications for synaptic dysfunction related to dementia.…”
Section: Accumulation Of Tau After Tbi and Risk For Cte-mentioning
confidence: 99%